Pemahaman Kata GO’EL Dalam Kitab Rut - Ponco Mujiono Basuki (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2018)
God is fully sovereign over the life of His people and He allows everything happening naturally in everyday man experience. But it will be real when examined more deeply, that in all the events of this life, God works to achieve His plan. Practically-theologically, the law about go’el in Israel's history is showing about the love and care of God in the Israel’s life, His people and proof of God's loyalty to His promises and plans. As go’el Boas also had to take Ruth to be his wife in order to uphold the name of the dead person, namely Mahlon, Ruth's husband, through the son who was born to Ruth from Boaz. Thus the name of Mahlon did not disappear from among the Israelites.